Effects of speech-based intervention with positive comments on reduction of driver's anger state and perceived workload, and improvement of driving performance. (July 2020) - Li, Shuling; Zhang, Tingru; Zhang, Wei; Liu, Na; Lyu, Gaoyan
Abstract: Research suggests that speech-based interventions can mitigate driving anger and enhance road safety. The present study found that both positive and negative comments can reduce anger state and perceived workload, and improve driving performance. In addition, positive comment including description of the driving environment and comment on drivers is more effective than negative comment intervention, which is indicated by larger effect size and higher user satisfaction and acceptance. The research findings could provide practical implications on the design of in-vehicle intelligent agents for driving behavior intervention. Highlights: Positive and negative comment interventions can reduce anger state and perceived workload, and improve driving performance. Participants who received positive comment intervention perform better than those who received negative comment intervention. Positive comment can be considered as a better content type for the design of in-vehicle intelligent agents for driving behavior intervention.